Architectural sites of discrimination: Positive to negative - Smith, Dianne (2018)
Architecture and interior settings are important aspects of everyday life for people with disabilities. An environmental situation consists of the contextually located architectural envelope, the interior – as well as constituent parts such as furniture – as well as its occupants. The physical environment can be an enabler for those who have impairments – the environmental concepts of space and place are thus implicated in the discourse of disability. Architecture and interior settings are important aspects of everyday life for people with disabilities. Places where author reside, study, shop, recuperate and play provide a multitude of possibilities for each and every one of them. Concurrently, these same places are sites of differentiation and discrimination – opportunities to interpret and judge are inherent. In the field of design for people with disabilities, these assumptions and expectations are underpinned by the same principles, and are just as important.